2011
DOI: 10.1152/japplphysiol.00128.2010
|View full text |Cite
|
Sign up to set email alerts
|

Intragastric administration of capsiate, a transient receptor potential channel agonist, triggers thermogenic sympathetic responses

Abstract: The sympathetic thermoregulatory system controls the magnitude of adaptive thermogenesis in correspondence with the environmental temperature or the state of energy intake and plays a key role in determining the resultant energy storage. However, the nature of the trigger initiating this reflex arc remains to be determined. Here, using capsiate, a digestion-vulnerable capsaicin analog, we examined the involvement of specific activation of transient receptor potential (TRP) channels within the gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
72
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(75 citation statements)
references
References 69 publications
(112 reference statements)
0
72
0
3
Order By: Relevance
“…Ono et al reported that prolonged treatment of rats with capsinoids resulted in increased UCP1 expression and decreased body fat (14). Body fat reduction and increased EE were also shown after capsinoid treatment for 12 weeks in mildly obese human subjects (20).…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…Ono et al reported that prolonged treatment of rats with capsinoids resulted in increased UCP1 expression and decreased body fat (14). Body fat reduction and increased EE were also shown after capsinoid treatment for 12 weeks in mildly obese human subjects (20).…”
Section: Resultsmentioning
confidence: 98%
“…To explore more practical methods for the recruitment of BAT, we focused on the chemical stimulants of TRP channels, particularly capsinoids. Because capsinoids activate TRPV1 and TRPA1 (13) and increase BAT thermogenesis (14,19), we reasoned that long-term capsinoid treatment could possibly recruit BAT in humans, as chronic cold exposure does.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In adult humans, a 4-wk treatment with CSNs was found to increase oxygen consumption, and a 12-wk treatment decreased the abdominal fat mass in subjects with body mass indexes (BMIs) of 25-35 (15, 50). Mechanistically, oral CSN supplements have been reported to activate transient receptor potential vanilloid subtype 1 (TRPV1) in the gut (14,47), resulting in increased sympathetic efferent activity and thermogenesis (41). Activation of TRPV1 signaling has been reported to positively regulate exercise endurance and energy expenditure in mice (30).…”
mentioning
confidence: 99%